Contribution à l’étude de l’effet des régimes additionnés de gland et de bentonite sur la qualité microbiologique de l’environnement d’élevage des poulets de chair élevés au sol et en batterie - AMRANE, Mansouria; Souafi, Bakhta (My University, 2019)
Bentonite has often been used in animal feed, particularly in poultry, and is known for its beneficial effects on zoo technical performance. The purpose of this study is to evaluate the effect of bentonite and glans on the microbiological quality of the litter and the levels of contamination of different surfaces with microbial germs (aerobic total mesophilic flora, total coliform, coliform fecal). , clostridium, sulfite reducer, yeast, mold and salmonella), as well as the evaluation of the effects of bentonite on the structure of droppings in soil and battery culture. The experiment was carried out on the farm of the University located in Hassi Mamèche - Mostaganem, The trial was started with a staff of 300 flesh chicks that are fed during the first 02 weeks of breeding with the diet start-up At the end of this period, 6 batches of 48 subjects each are made up of (homogeneous weight and same sex) and are nourished with the growth regime administered of glans and 2% calcium-like bentonite for a period of six weeks. A farm on the ground and in batteries were made. The experimental batches will include Control lot, Lot with 33% corn substitution by the glans, Lot with 33% corn substitution by the glans supplemented with 2% bentonite. It appears during the experimentation that the addition of the glans in the diet substantially reduces the level of contamination for the different surfaces and sample taking. Moreover, the addition of the associated glans of bentonite seems to give the best results to reduce the level of contamination by these germs, a decrease in the humidity of the droppings was recorded in the batches supplemented with the glans and bentonite, the results of the present experiment allowed to validate the effectiveness of the clays to improve the quality of the litter, Finally the breeding in battery to improve the sanitary state and the reduction of the environmental pollution compared to the breeding in soil.
Keywords: calcium bentonite; broiler chicken; growth; meat; mycotoxins; microbiological analyzes